NILAI-NILAI ALEMPURENG (KEJUJURAN) DALAM LONTARA LATOA TANA BONE PERSPEKTIF PENDIDIKAN ISLAM - L., Idrus (Atta'dib Jurnal Pendidikan Agama Islam, 2025)
This study aims to explore the value of alempureng (honesty)contained in Lontara Latoa Tana Bone and its relevance in thecontext of Islamic education. This research uses a qualitativeapproach with descriptive analysis to identify and understand howthe value of honesty is internalized in Bugis character education. Thefindings show that Lontara Latoa functions not only as a culturaltext, but also as a source of educational values that teach theimportance of honesty in social interaction and national life. Thevalue of alempureng in it acts as a moral foundation that supportsthe formation of good character, in line with the teachings of theQur'an and Hadith. This research recommends the integration ofvalues of honesty into the educational curriculum in order to developindividuals with integrity and high morals. Thus, this researchcontributes to the development of local and religious values-basedcharacter education, as well as strengthening the understanding ofthe importance of honesty in the context of Islamic education.Â